Pengaruh Kualitas Pelayanan dan Promosi terhadap Keputusan Pembelian Paket IndiHome di Telkomsel Banda Aceh: Analisis Regresi Linier Berganda - Nurbismi; Maulida, Zenitha; Madrul, Heqal (Jurnal EMT KITA, 2025)
The purpose of this study was to determine the effect of Service Quality and Promotion on the Purchase Decision of Indihome packages in Telkomsel Banda Aceh both partially and simultaneously. The number of samples in this study was 140 respondents. The method used in this study is a quantitative method. Research data were collected through questionnaires and analyzed using multiple linear regression models and processed using the SPSS (Statistic Package for Social Science) assistance program. Hypothesis testing using multiple linear regression analysis, t-test and F-test is intended to determine simultaneously and partially the effect of independent variables on the dependent variable at the confidence level 95% (α = 0.05). The results of this study based on simultaneous tests indicate that the variables of Service Quality and Promotion influence the Purchase Decision of Indihome packages in Telkomsel Banda Aceh. Then based on partial tests that Service Quality and Promotion have an effect on the Purchase Decision of Indihome packages in Telkomsel Banda Aceh. Suggestions that can be given to Telkomsel are to continuously improve the quality of service by providing a fast response to complaints from Indihome customers and developing infrastructure with adequate modernization network expansion so that the connection is stable and adequate promotion so that customers do not switch to other products.
Keywords: Service Quality; Promotion; Purchasing Decisions; Indihome; Telkomsel